Green education : an A-to-Z guide - Newman, Julie (Sage reference series on green society.)
This volume explores the environmental movement's proliferation in the field of education, from elementary school classroom efforts to the university curriculum to building sustainable campuses. Focusing on the critical role of education in building a sustainable future, approximately 150 signed entries, written by scholars and experts in a variety of disciplines, examine school and college courses in green education, the structures of educational institutions, the challenges of reducing their ecological footprint, administrative policies, green campus organizations, and student and faculty participation. The editors have included photographs, hyperlinks, cross references, and a resource guide.